GENOTYPIC, PHENOTYPIC CORRELATIONS AND PATH COEFFICIENT ANALYSIS IN COTTON. - Mohammed, Layla I.; Al-Marsoomi, Abd-Aljelil (Diyala Agricultural Sciences Journal, 2011)
Field experiment was carried out at State Board for Agricultural Researches. The objectives were to study genotypic and phenotypic correlations and path coefficient analysis for eighteen characters included growth, yield and its components, and fiber quality traits for 9 varieties (Marsoomi-4, Ashur-1, Abu Ghraib-5, Cocker-310, Lashata, Kafco-1, Pamir, Rabia-122, Pac-cot- 189) of cotton (Gossypium hirsutum L.), its crosses and reciprocal crosses. The traits for 72 single crosses and 9 parents were tested during 2002 using partially balanced Triple Lattice Design with three replications. Results of genotypic and phenotypic coefficient correlation values were obtain for lint yield with seed cotton (0.933 and 0.914 respectively), number of open bolls (0.559 and 0.546 respectively), number of sympodial, seed index, plant height, and recently fineness. path coefficient analysis revealed that plant lint yield and number of open bolls obtain highest positive direct effect in seed cotton were 0.947 and 0.402 respectively then number of seeds per boll and highest positive indirect effect through lint yield. Can be conclude to use lint yield and number of open yield as a selection criteria because it gave highly positive genetic correlation and highly direct effect depending upon results of genotypic and phenotypic correlations and path coefficient analysis.